2020
DOI: 10.1111/dth.13203
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of topical ivermectin and impact on quality of life in patients with papulopustular rosacea: A systematic review and meta‐analysis

Abstract: Rosacea is a chronic dermatosis which affects negatively patients' quality of life (QoL).There is shortage of high-quality evidence comparing the efficacy of ivermectin cream (IVM) 1% with other available topical choices. Besides, the well-documented impaired of self-esteem and stigmatization of rosacea patients make essential to address which treatment provides the greatest psychological and social benefit. Our objective is to critically review and appraise the efficacy of IVM 1% in PPR and the impact in pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 34 publications
1
19
0
5
Order By: Relevance
“…Laboratory results further support the clinical findings, since in our study severity scores and DLQI worsened in both acne and rosacea patients after 6 weeks of masks, in agreement with previous reports described a detrimental influence on quality of life in patients affected by these dermatoses 24,25 …”
Section: Discussionsupporting
confidence: 92%
“…Laboratory results further support the clinical findings, since in our study severity scores and DLQI worsened in both acne and rosacea patients after 6 weeks of masks, in agreement with previous reports described a detrimental influence on quality of life in patients affected by these dermatoses 24,25 …”
Section: Discussionsupporting
confidence: 92%
“…Topical azelaic acid (high-certainty evidence), topical ivermectin (high-certainty evidence), topical metronidazole (moderate-certainty evidence), and topical minocycline (moderate-certainty evidence) were recommended for the treatment of papules/pustules [19]. In a systematic review and meta-analysis, topical ivermectin was demonstrated to be the most effective topical treatment for papulopustular rosacea and to provide the greatest psychological benefit to these patients [29]. Topical ivermectin can be applied not only to skin almost clear of papulopustular rosacea or with mild rosacea, but also to skin with moderate to severe rosacea [4].…”
Section: Topical Therapiesmentioning
confidence: 99%
“…In a recent meta-analysis, topical ivermectin 1 % was mentioned as the best topical approach for PPR [14]. Ivermectin has a dual effect on PPR, by inhibiting critical pathways of the inflammatory response and reducing the density of the Demodex mite [49], and topical ivermectin 1 % has been Figure 3 Results of the overall meta-analysis including comparative studies of SDD versus placebo and studies of SDD versus active drugs (a).…”
Section: Discussionmentioning
confidence: 99%